2014
DOI: 10.1039/c3cp55319a
|View full text |Cite
|
Sign up to set email alerts
|

Spin polarization gives rise to Cu precipitation in Fe-matrix

Abstract: This article tries to uncover the physical reason of Cu precipitation from an Fe matrix at the electronic level. The general rule is obtained that the more bonds among Cu atoms, the more stable the system is. It was shown that Cu would precipitate from the matrix with Fe spin-polarization but not without spin-polarization. The partial density of states (PDOS) analysis illustrated that the d states of Fe near the Fermi level potentially have strong interaction with other atoms, but Cu d states below the Fermi l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…In the COHP curve of Figure 5 , it is notable that the Fermi level passes through the antibonding area of all the bonds ( Song and Zhao, 2014 ), and there are some antibonding states present below the Fermi level. This is because the atomic radius of Pt is much larger than that of Co.…”
Section: Resultsmentioning
confidence: 99%
“…In the COHP curve of Figure 5 , it is notable that the Fermi level passes through the antibonding area of all the bonds ( Song and Zhao, 2014 ), and there are some antibonding states present below the Fermi level. This is because the atomic radius of Pt is much larger than that of Co.…”
Section: Resultsmentioning
confidence: 99%
“…The figures in bold indicate the formation energy lower than that of pure cluster, À0. 34 9,[19620][19621][19622][19623][19624][19625][19626][19627][19628][19629] This journal is © The Royal Society of Chemistry 2019 the latter. It reects that the hardening effect of Mn on alloys is mainly induced by the grain renement and the increased number density of precipitates.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that the dependence of phase separation tendency between Fe and Cu on temperature is more related to the magnetic phase transition compared to vibrational contribution. [33][34][35][36] The calculations of elastic properties of bulk FeCu phase revealed that only FeCu with Cu content below 50% is mechanically stable; 37 the segregation of alloying elements, such as Ni, Al, Mn, etc., was conrmed to derive from thermodynamic factors, 27,38 and the segregation behaviors can change strain and chemical interactions at interfaces, resulting in the reduction of interface energy. 39 Since point defects are tightly related to the microstructure evolution of steels, many studies were performed to reveal the interaction between point defects in body-centered cubic (bcc) Fe toward understanding the formation of precipitates.…”
Section: Introductionmentioning
confidence: 99%
“…There may be some ways to approach the electronic aspect of the catalytic activity of β-PtO 2 . In this study, we have made good use of a powerful band-decomposition tool called crystal orbital overlap population (COOP). , COOP can be viewed as a partial density of states for a pair of atoms weighted with the corresponding Mulliken overlap population. , COOP is plotted as a function of energy, providing a simple graphical representation as to whether the interaction between the pair of atoms exhibits a bonding character or antibonding one at a certain energy level: positive COOP values indicate bonding interactions, while negative values indicate antibonding interactions.…”
Section: Theoretical Methodsmentioning
confidence: 99%